2016
DOI: 10.1051/0004-6361/201527021
|View full text |Cite
|
Sign up to set email alerts
|

Effects of environmental gas compression on the multiphase ISM and star formation

Abstract: The cluster environment can affect galaxy evolution in different ways: via ram pressure stripping or by gravitational perturbations caused by galactic encounters. Both kinds of interactions can lead to the compression of the interstellar medium (ISM) and its associated magnetic fields, causing an increase in the gas surface density and the appearance of asymmetric ridges of polarized radio continuum emission. New IRAM 30m HERA CO(2−1) data of NGC 4501, a Virgo spiral galaxy currently experiencing ram pressure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
40
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 53 publications
4
40
1
Order By: Relevance
“…However, a decrease of the depletion time as observed, e.g. in LIRGs (Klaas et al 2010;Martinez-Badenes et al 2012;Nehlig et al 2016) translates into a deviation from this relation. A duality of star formation regimes has been proposed by Daddi et al (2010b) to distinguish galaxies with long and short depletion times, respectively disks and mergers, but independently of their SFR.…”
Section: Introductionmentioning
confidence: 86%
“…However, a decrease of the depletion time as observed, e.g. in LIRGs (Klaas et al 2010;Martinez-Badenes et al 2012;Nehlig et al 2016) translates into a deviation from this relation. A duality of star formation regimes has been proposed by Daddi et al (2010b) to distinguish galaxies with long and short depletion times, respectively disks and mergers, but independently of their SFR.…”
Section: Introductionmentioning
confidence: 86%
“…Surveys of nearby galaxies show a scatter in τ depl of ∼ 0.3 dex at galactic and sub-galactic scales (Saintonge et al 2011;Leroy et al 2013). However, interacting starburst galaxies (Klaas et al 2010;Nehlig et al 2016;Saito et al 2016) and ultra-luminous infrared galaxies (LIRGs, ULIRGS; Saintonge et al 2011;Martinez-Badenes et al 2012) exhibit a lower systematic τ depl of 0.05-0.8 Gyr.…”
Section: Introductionmentioning
confidence: 99%
“…Ram pressure, as another external force, is known for quenching star formation, particularly in dwarf galaxies (Steinhauser et al 2016), but can also locally compress gas and have the opposite effect (Ebeling et al 2014), especially in more massive systems where the background potential helps slowing down gas stripping. Studies of τ depl in galaxies at various stages of interaction indicate that the tidal gravitational forces change τ depl up to 0.4 dex (Martinez-Badenes et al 2012;Nehlig et al 2016;Lee et al 2017). Nehlig et al (2016) observed that ram pressure can decrease τ depl , but not as effectively as the tidal effects.…”
Section: Introductionmentioning
confidence: 99%
“…This leads to ISM compression and increasing H 2 formation; hence, it locally triggers intensive star formation (Fujita & Nagashima 1999;Kronberger et al 2008;Merluzzi et al 2013;Henderson & Bekki 2016). Indeed, ISM compression with high molecular fraction in the upstream side is seen in a number of galaxies experiencing ICM pressure (Vollmer et al 2012b;Nehlig, Vollmer & Braine 2016), which are often accompanied by an enhancement of star formation. Molecular gas enhancement among the Virgo cluster members has been also recently reported by Mok et al (2016).…”
Section: Introductionmentioning
confidence: 99%